PARTISIPASI MASYARAKAT DALAM PENYUSUNAN RENCANA KERJA PEMERINTAH DAERAH KOTA PONTIANAK PROVINSI KALIMANTAN BARAT TAHUN 2016 - Sujendra, Bima (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2016)
Public Participation in Local Government Planning Work Pontianak province of West Kalimantan in 2016 was chosen because the researchers are encouraged by the phenomenon of community participation in implementation RKPD Musrenbang for the preparation of the proposal is still lacking and many people who do not direalisaikan. To that end, the general research problem is formulated: